No evidence for preferential X-chromosome inactivation as the main cause of divergent phenotypes in sisters with X-linked hypohidrotic ectodermal dysplasia - Körber, Laura; Schneider, Holm; Fleischer, Nicole; Maier-Wohlfart, Sigrun (Orphanet Journal of Rare Diseases, 2021)
Background: X-linked hypohidrotic ectodermal dysplasia (XLHED), a rare genetic disorder, affects the normal development of ectodermal derivatives, such as hair, skin, teeth, and sweat glands. It is caused by pathogenic variants of the gene EDA and defined by a triad of hypotrichosis, hypo- or anodontia, and hypo- or anhidrosis which may lead to life-threatening hyperthermia. Although female carriers are less severely affected than male patients, they display symptoms, too, with high phenotypic variability. This study aimed to elucidate whether phenotypic differences in female XLHED patients with identical EDA genotypes might be explained by deviating X-chromosome inactivation (XI) patterns. Methods: Six families, each consisting of two sisters with the same EDA variant and their parents (with either mother or father being carrier of the variant), participated in this study. XLHED-related data like sweating ability, dental status, facial dysmorphism, and skin issues were assessed. We determined the women`s individual XI patterns in peripheral blood leukocytes by the human androgen receptor assay and collated the results with phenotypic features. Results: The surprisingly large inter- and intrafamilial variability of symptoms in affected females was not explicable by the pathogenic variants. Our cohort showed no higher rate of nonrandom XI in peripheral blood leukocytes than the general female population. Furthermore, skewed XI patterns in favour of the mutated alleles were not associated with more severe phenotypes. Conclusions: We found no evidence for preferential XI in female XLHED patients and no distinct correlation between XLHED-related phenotypic features and XI patterns. Phenotypic variability seems to be evoked by other genetic or epigenetic factors.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Ectodysplasin A; Female carriers; Genotype–phenotype correlation; X-chromosome inactivation; X-linked hypohidrotic ectodermal dysplasia